FENOMENA FEAR OF MISSING OUT (FOMO) PADA MAHASISWA PENGGUNA MEDIA SOSIAL DI PROGRAM STUDI BIMBINGAN DAN KONSELING UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Rindia Septa Kurnia; M. Arif; Yeni Afrida; Sri Hartati (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This study aims to explore the phenomenon of Fear of Missing Out (FoMO) among students who use social media in the Guidance and Counseling Study Program of the Sjech M. Djamil Djambek State Islamic University Bukittinggi, especially for the 2021, 2022, and 2023 intakes. Using a quantitative descriptive method, this study involved 376 students as the population, and 183 students were selected as samples through a proportional random sampling technique. Data were collected using a FoMO questionnaire that had gone through a validation and reliability process by experts. The results of the analysis showed that 48.6% of students were in the high category in the FoMO experience. Specifically, the worry indicator had an average of 30.4 with a percentage of 61.58%, and a standard deviation of 7.291, indicating that students were very worried about missing important information or experiences. In addition, the indicator recorded an average fear of 20.70 with a percentage of 59.19% and a standard deviation of 4.580, indicating a moderate level of fear. Meanwhile, the anxiety indicator shows an average of 12.36 with a percentage of 61.80% and a standard deviation of 3.083, placing anxiety in the high category.